A new perspective on mechanical characterisation of Arabidopsis stems through vibration tests. (December 2020) - Zhdanov, Oleksandr; Blatt, Michael R.; Cammarano, Andrea; Zare-Behtash, Hossein; Busse, Angela
Abstract: The mechanical properties of plants are important for understanding plant biomechanics and for breeding new plants that can survive in challenging environments. Thus, accurate and reliable methods are required for the determination of mechanical properties such as stiffness and Young's modulus of elasticity. Much attention has been paid to the application of static methods to plants, while dynamic methods have received considerably less attention. In the present study, a dynamic forced vibration method for mechanical characterisation of Arabidopsis inflorescence stems was developed and validated against the conventional three-point bending test. Compared to dynamic tests based on free vibration, the current method allows to determine simultaneously more than one natural frequency, thus increasing the overall accuracy of the results. In addition, this method can be applied to the top parts of the stems that are more flexible, and where application of the three-point bending test is often limited. To demonstrate one of the potential applications of this method, it was applied to evaluate the influence of turgor pressure on the mechanical properties of Arabidopsis stems. Overall, the new dynamic testing approach has been shown to provide reliable data for the local mechanical properties along the Arabidopsis inflorescence stem. Graphical abstract: Image 1 Highlights: A forced vibration method for mechanical testing of Arabidopsis stems was developed. The method was validated against the conventional three-point bending test. Mechanical properties of the bottom and top parts of the stem differ significantly.